233k views
2 votes
Question 5 (2 points)

Tony solves the linear equation 3(x-3) + 2x + 9 = 2x + 2(x - 1) using the step shown below.
Step 1: 3 - 3 + 2x + 9 = 2x + 2x - 1
Step 2: 5x + 6 = 4x - 1
Step 3: 5x - 4x = -1 -6
Step 4: x=-7
OOOO
He incorrectly applied the multiplication and division properties of equality.
He distributed incorrectly.
He incorrectly applied the addition and subtraction properties of equality.
He incorrectly combined like terms.
c

1 Answer

1 vote

Answer:

c cuh

Explanation:

(idk the answer)

User Kewal Shah
by
5.4k points